The taxonomic implication of frontal tubercles in Polypedilum subgenera diagnoses, with re-description of Polypedilum isigabeceum Sasa & Suzuki (Diptera, Chironomidae) - Yamamoto, Nao; Yamamoto, Masaru (Zootaxa, 2016)
Polypedilum isigabeceum Sasa et Suzuki, 2000 was described as belonging to subgenus Polypedilum s. str. However, if we accept the conclusion of Sæther et al. (2010), the species might be placed into Kribionympha with P. unagiquartum Sasa, 1985 because of the presence of distinct frontal tubercles in the adult males. However, other taxonomic characters do not support their treatment. P. isigabeceum is re-described and reconfirmed to be assigned to the subgenus Polypedilum s. str. The taxonomic meaning of frontal tubercles is discussed for defining the subgeneric rankings within genus Polypedilum.